Desmoid-type fibromatosis of transverse mesocolon - Martins Rodrigues, Ana Catarina; Cardoso, Mónica; Gil Alves, Duarte; Fernandes, Sara; Olim Sousa, Maria; Fernandes, Jorge; Caldeira, Carmo; Caires, António Girão (International Surgery Journal, 2023)
Desmoid tumors represent a rare disease. The recommendations for treatment and approach of these neoplasms are sparse. There are no specific imaging or clinical features which turns the diagnosis difficult. A 53-year-old male patient presented with complaints of peri-umbilical abdominal pain associated with a palpable mass. CT scan revealed a heterogeneous mass with soft tissue density and well-defined contour with approximately 8.5×7×5.3 cm localized in the mesogastric region with apparent origin in the transverse colon. The purposed etiology was of GIST. Colonoscopy was normal. The patient was submitted to surgery which revealed a mass with bright and smooth surface that was in relation with the mid portion of the transverse colon, we performed a right extended hemicolectomy. The postoperative was uneventful. Pathology evaluation revealed a desmoid-type fibromatosis. The accurate etiology of desmoid tumors is still unknown. Desmoid tumors are rare with an annual incidence of 2-4 cases per million people. They typically are slow growing fibrous soft tissue tumors with a benign behavior, however show local aggressiveness with a high ability for recurrence, complete surgical resection with clear margins is crucial.